One-pot preparation of trifluoromethylated homoallylic N-acylhydrazines or α-methylene-γ-lactams from acylhydrazines, trifluoroacetaldehyde methyl hemiacetal, allyl bromide and tin. Issue 4 (22nd December 2015) - Du, Ganggang; Huang, Danfeng; Wang, Ke-Hu; Chen, Xiaowei; Xu, Yanli; Ma, Junyan; Su, Yingpeng; Fu, Ying; Hu, Yulai
Abstract : Tin promoted one-pot preparation of trifluoromethylated homoallylic N -acylhydrazines or α-methylene-γ-lactams has been developed instead of using toxic stannanes. Abstract : An efficient and convenient one-pot method for the preparation of trifluoromethylated homoallylic N -acylhydrazines or α-methylene-γ-lactams has been described. In this process, allyl bromide and metal tin are used instead of toxic stannanes, and commercially available aqueous trifluoroacetaldehyde methyl hemiacetal was used as a trifluoromethyl source.